Ultrasound-guided assessment of gastric volume in fasting diabetic and non-diabetic patients undergoing elective surgery - Sumedha Dhar; Debasish Ghosh; Soma Chakraborty; Sandesh Rathod; Navneet Kumar; Debasish Saha (Asian Journal of Medical Sciences, 2025)
Background: Autonomic gastropathy despite standard fasting in diabetic patients increases the risk of aspiration. Aims and Objectives: This study compared ultrasound-guided measurement of residual gastric volume (GV) between diabetic and non-diabetic patients scheduled for elective surgery. Materials and Methods: The study was a prospective observational study carried out on 42 patients with similar demographic characteristics, having similar fasting intervals >8 hours. Qualitative and quantitative ultrasonographic assessment of gastric antrum in supine and right lateral decubitus (RLD) was done 1 hour before induction of anesthesia using a curved array, low-frequency transducer. Ultrasonography grade, cross-sectional area (CSA) of the antrum, and GV were calculated. The gastric antral appearance was classified as Grade 0, 1, or 2, signifying empty antrum, fluid in RLD position only, and fluid in both supine and RLD positions, respectively. Result: Diabetic patient had higher median GV and a wider interquartile range than the non-diabetic patients suggesting delayed gastric emptying in diabetics. The mean diameters of both anteroposterior and craniocaudal and CSA calculated in both supine and RLD positions had a statistically significant difference with a higher value observed in the diabetic group as compared to the non-diabetic group (P<0.001). Conclusion: Diabetic patients have higher GVs and gastric antral CSA than non-diabetic patients signifying delayed gastric emptying. Qualitative grading may be useful for screening purposes but quantitative analysis provides a more reliable estimate of GV. Gastric ultrasound is a valuable tool in identifying the risk of pulmonary aspiration thus helping in pre-operative decision-making.